Calcium‐sensing receptor regulates intestinal dipeptide absorption via Ca2+ signaling and IKCa activation. Issue 1 (21st January 2020) - Xu, Jingyu; Zeug, Andre; Riederer, Brigitte; Yeruva, Sunil; Griesbeck, Oliver; Daniel, Hannelore; Tuo, Biguang; Ponimaskin, Evgeni; Dong, Hui; Seidler, Ursula
Abstract: Although absorption of di‐ and tripeptides into intestinal epithelial cells occurs via the peptide transporter 1 (PEPT1, also called solute carrier family 15 member 1 (SLC15A1)), the detailed regulatory mechanisms are not fully understood. We examined: (a) whether dipeptide absorption in villous enterocytes is associated with a rise in cytosolic Ca 2+ ([Ca 2+ ]cyt ), (b) whether the calcium sensing receptor (CaSR) is involved in dipeptide‐elicited [Ca 2+ ]cyt signaling, and (c) what potential consequences of [Ca 2+ ]cyt signaling may enhance enterocyte dipeptide absorption. Dipeptide Gly‐Sar and CaSR agonist spermine markedly raised [Ca 2+ ]cyt in villous enterocytes, which was abolished by NPS‐2143, a selective CaSR antagonist and U73122, an phospholipase C (PLC) inhibitor. Apical application of Gly‐Sar induced a jejunal short‐circuit current ( Isc ), which was reduced by NPS‐2143. CaSR expression was identified in the lamina propria and on the basal enterocyte membrane of mouse jejunal mucosa in both WT and Slc15a1 −/− animals, but Gly‐Sar‐induced [Ca 2+ ]cyt signaling was significantly decreased in Slc15a1 −/− villi. Clotrimazole and TRM‐34, two selective blockers of the intermediate conductance Ca 2+ ‐activated K + channel (IKCa ), but not iberiotoxin, a selective blocker of the large‐conductance K + channel (BKCa ) and apamin, a selective blocker of the small‐conductance K + channel (SKCa ), significantly inhibited Gly‐Sar‐induced Isc in native tissues. We reveal a novel CaSR‐PLC‐Ca 2+ ‐IKCa pathway in the regulation of small intestinal dipeptide absorption, which may be exploited as a target for future drug development in human nutritional disorders. Abstract : What is already known: The H + /dipeptide absorption rates in the small intestine depend on the maintenance of a negative membrane potential rather than the transmembrane proton gradient. What this study adds: The CaSR mediates intestinal dipeptide absorption through the Ca 2+ /IKCa/hyperpolarization mechanism Clinical significance: CaSR‐PLC‐Ca 2+ ‐IKCa pathway could be exploited as a potential target in human nutritional disorders.